2020
DOI: 10.1200/jco.2020.38.15_suppl.12012
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of a perioperative geriatric intervention for older adults with cancer.

Abstract: 12012 Background: Older adults with gastrointestinal (GI) cancers undergoing surgery often experience poor outcomes, such as prolonged postoperative (post-op) length of stay (LOS), intensive care unit (ICU) use, and readmissions. Involvement of geriatricians in the care of older adults with cancer can improve outcomes. We conducted a randomized trial of a perioperative geriatric intervention in older adults with GI cancers undergoing surgery. Methods: We randomly assigned patients age ≥65 with GI cancers plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The results showed that interventions based on preoperative GA did not reduce the incidence of grade II-IV adverse events 15 . Currently, there are several randomized controlled trials evaluating the usefulness of preoperative GA for elderly cancer surgery patients, and the results are promising 16 , 17 . However, differences in the background of the study population, selection bias, surgical techniques and assessment tools used, as well as endpoints, make it difficult to build evidence, and this is an issue that should be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that interventions based on preoperative GA did not reduce the incidence of grade II-IV adverse events 15 . Currently, there are several randomized controlled trials evaluating the usefulness of preoperative GA for elderly cancer surgery patients, and the results are promising 16 , 17 . However, differences in the background of the study population, selection bias, surgical techniques and assessment tools used, as well as endpoints, make it difficult to build evidence, and this is an issue that should be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence from other trials of predominantly solid tumors suggests that GAdriven interventions improve meaningful outcomes other than survival in older patients with cancer, including decreased treatment toxicity and improvements across multiple domains of quality of life. 16,17,27,28,36,37 Varying models of GA-driven interventions were studied in these trials, ranging from a GA summary with recommended interventions carried out by the treating hematologic oncologist, to an embedded co-management model led by a geriatrician (as described above). Future trials in older adults with blood cancers should investigate not only the effectiveness of different models of geriatrics-driven interventions in terms of mortality, but also their impact on treatment decisions and patient-centered outcomes such as function and quality of life-outcomes often valued by older patients just as much as if not more than survival.…”
Section: Discussionmentioning
confidence: 99%
“…Although GA observational studies and case control studies in elderly cancer surgery patients are increasing, differences in study population background, selection bias, surgical techniques and evaluation tools used, and endpoint settings make it di cult to build the evidence. In such a situation, four randomized control studies as new evidence for GA were reported at the ASCO 2020 annual meeting [ [12][13][14][15] ]. Three of the four studies were chemotherapeutic studies and the remaining was a surgical study; all showed the usefulness of the GA.…”
Section: Discussionmentioning
confidence: 99%